Association between STK11 Gene Polymorphisms and Coronary Artery Disease in Type 2 Diabetes in Han Population in China. (28th February 2017) - Ma, Xiaowei; Bai, Ge; Lu, Difei; Huang, Linjuan; Zhang, Jianwei; Deng, Ruifen; Ding, Shan; Gu, Nan; Guo, Xiaohui
Abstract : Background . Recent studies indicated that the Serine threonine kinase 11 (STK11), which is a key regulator of the AMP-activated protein kinase (AMPK), plays a crucial role in cardiovascular system. This study aimed to investigate whether genetic variations in the STK11 gene affect the risk of coronary artery disease (CAD) in Chinese type 2 diabetics. Methods . 5 haplotype-tagging single nucleotide polymorphisms (SNPs) were selected, and 288 CAD-positive cases and 159 CAD-negative controls with type 2 diabetes were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. Results . The carriers of minor allele A at rs12977689 had a higher risk of CAD compared to the homozygotes of CC (OR = 1.572, 95% CI = 1.039–2.376, p = 0.035 ), and the difference was still significant after adjustment for the other known CAD risk factors (O R ′ = 1.184, 95%  C I ′ = 1.036–1.353, p ′ = 0.013 ). Conclusion . Genetic variability at STK11 locus is associated with CAD risk in type 2 diabetes in the Chinese population.